Penggunaan Lagu Anak Islami terhadap Penguasaan Kosakata Anak Usia Dini - Febry Wahyuni Lubis; Syamsiah Depalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the effect of the use of Islamic children's songs on vocabulary mastery in early childhood. Vocabulary is a key element in children's language development, which greatly determines children's success in communicating and understanding their surroundings. Songs as a form of audio-visual media have proven effective in increasing children's language absorption because they are repetitive, rhythmic, and fun. This study uses a descriptive qualitative approach, data obtained through direct observation, teacher interviews, and documentation of the learning process. The results showed that Islamic children's songs significantly improved children's vocabulary mastery both in religious and general vocabulary contexts. Islamic songs strengthen children's memory of new words and enrich their verbal abilities in the context of learning and social interaction.